2021
DOI: 10.1021/acs.jafc.1c05070
|View full text |Cite
|
Sign up to set email alerts
|

Sublethal Exposure to Deltamethrin Stimulates Reproduction and Alters Symbiotic Bacteria in Aphis gossypii

Abstract: In aphids, hormesis and symbiotic bacteria are the drivers for the development of pesticide resistance. However, the related mechanism remains unclear. Here, we evaluated the sublethal and transgenerational effects of the extensively used pyrethroid pesticide deltamethrin (DMT) on the population dynamics in Aphis gossypii and tested its influence on symbiotic bacterial communities. The leaf-dip bioassay revealed that DMT was highly toxic to A. gossypii, and at a low lethal concentration of DMT, the intrinsic (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 58 publications
3
14
0
Order By: Relevance
“…Thus, pyridaben exposure led to reproduction stimulation on the F 1 generation of P. citri at LC 30 concentrations. Similar effects have been observed for several pesticides like sulfoxaflor, deltamethrin, and acetamiprid on A. gossypii 48,49,61 . Age‐specific fecundity ( m x ), age‐specific net maternity ( l x m x ), and age‐specific reproductive value ( v xj ) parameters can provide important details regarding the reproductive capacity of pest populations.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Thus, pyridaben exposure led to reproduction stimulation on the F 1 generation of P. citri at LC 30 concentrations. Similar effects have been observed for several pesticides like sulfoxaflor, deltamethrin, and acetamiprid on A. gossypii 48,49,61 . Age‐specific fecundity ( m x ), age‐specific net maternity ( l x m x ), and age‐specific reproductive value ( v xj ) parameters can provide important details regarding the reproductive capacity of pest populations.…”
Section: Discussionsupporting
confidence: 61%
“…Similar effects have been observed for several pesticides like sulfoxaflor, deltamethrin, and acetamiprid on A. gossypii. 48,49,61 Age-specific fecundity (m x ), age-specific net maternity (l x m x ), and age-specific reproductive value (v xj ) parameters can provide important details regarding the reproductive capacity of pest populations. The m x , l x m x and v xj parameters of F 1 generation P. citri individuals exposed to LC 30 levels of pyridaben were higher than those of the controls for the pyridaben-resistant strain.…”
Section: Discussionmentioning
confidence: 99%
“…However, it offers an appropriate environment that stimulates the proliferation and diversification of insect gut microbiomes ( Bruno et al, 2019 ). Many studies have reported that insect gut microbiota plays a significant role in developing symbiotic insect interactions facilitated by secondary metabolites ( Shang et al, 2021a ). Besides this, they also play an essential role in the detoxification of pesticides, providing a natural defense system, nutrient availability, development of resistance against toxins and pathogens, breakdown of food, and suitable for proper growth of insects ( Jang and Kikuchi, 2020 ; Jing et al, 2020 ; Mogren and Shikano, 2021 ; Tilottama et al, 2021 ).…”
Section: Functions Of Insect Gut Microbiotamentioning
confidence: 99%
“…104 As in the present study, increased abundance of a few phyla or species of symbionts in a particular sublethal treatment group has been previously reported in other pest insect, A. gossypii. 105 Furthermore, earlier research has demonstrated that xenobiotic stress can cause changes in abundance of symbionts in soybean aphids. 106…”
Section: Discussionmentioning
confidence: 99%